DISTRIBUTION SPATIALE DE RHADINORHYNCHUS CADENATI PARASITES INTESTINAL DE POISSON TRACHINOTUS OVATUS DE LA CÃ”TE DE MEHDIA (MAROC) - Elmadhi, Youssef; Hassouni, Taoufik; Lamri, Driss; Chiahou, Brahim; Darif, Hajar; Shawket, Nizar; Youssir, Sanaa; El Kharrim, Khadija; Belghyti, Driss (European Scientific Journal, ESJ, 2015)
Rhadinorhynchus cadenati and and Pomphorhynchus Francoise are two parasitic Acanthocephala Trachinotus ovatus from the Atlantic coast of Mehdia (Morroco). They always locate at the gut and they occupy almost the same habitat. Rhadinorhynchus cadenati is the most abundant and it is with great numbers, that is why we are interested to follow its spatial distribution along the intestine of host fish T. ovatus.